Comparison of Inhibition Zones Between Butterfly Pea Flower (Clitoria ternatea) and Lemongrass (Cymbopogon citrarus) Against Streptococcus mutans and Staphylococcus aureus - Haditio, Steven Martin; Zulfan Muttaqin; Lina Hadi (Fakultas Kedokteran Universitas Sriwijaya (Faculty of Medicine, Universitas Sriwijaya) Indonesia, 2021)
This study aims to determine the comparison of the inhibition zone between theextract of butterfly pea flower and lemongrass, against the bacteria streptococcusmutans and staphylococcus aureus. The samples that will be used in this researchare streptococcus mutans and staphylococcus aureus bacteria. Data analysis usednormality test and statistical test was performed using ANOVA analysis test and posthoc test. The results showed that there was no difference in the inhibition zone ofbutterfly pea flower extract against streptococcus mutans bacteria and lemongrassextract against streptococcus mutans. There was difference in the inhibition zonebetween butterfly pea flower extract against staphylococcus aureus bacteria andlemongrass extract against staphylococcus aureus bacteria. Butterfly pea flowerextract has a good inhibition zone in staphylococcus aureus bacteria. Lemongrassextract has the same inhibition zone against both types of bacteria